Determinan Kinerja Keuangan Pada Perusahaan Sektor Consumer Cyclicals di BEI Periode 2021-2023 - Widyastuti, Riris Retno; Paramitalaksmi, Ratri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Financial performance reflects the company's success rate in managing business activities to achieve the goal of making a profit. Financial performance serves as a benchmark to measure the company's ability to optimize its resources to create added value for all stakeholders. This study aims to find evidence regarding various factors that affect the financial performance of companies listed on the Indonesia Stock Exchange. In this study, the factors tested include financial ratios, which include profitability, liquidity, solvency, activity, valuation, and growth. In this study, the object is companies in the consumer cyclical sector listed on the IDX for 2021-2023. Purposive sampling is used as a method for selecting samples with a population of 21 companies and a sample size of 63. In addition, this study uses multiple linear regression analysis techniques with the help of SPSS software version 27. The study's results prove that profitability, solvency, and growth do not affect the financial performance of companies in the consumer cyclical sector. In contrast liquidity, activity, and valuation are proven to affect the financial performance of companies in the consumer cyclicals sector.